2017
DOI: 10.1371/journal.pone.0178511
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing fish Underwater Visual Census to move forward assessment of fish assemblages: An application in three Mediterranean Marine Protected Areas

Abstract: Monitoring fish assemblages is needed to assess whether Marine Protected Areas (MPAs) are meeting their conservation and fisheries management goals, as it allows one to track the progress of recovery of exploited species and associated communities. Underwater Visual Census techniques (UVC) are used to monitor fish assemblages in MPAs. UVCs should be adapted to fish abundance, body-size and behaviour, which can strongly affect fish detectability. In Mediterranean subtidal habitats, however, UVC strip transects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 46 publications
(62 reference statements)
3
40
0
Order By: Relevance
“…All species were recorded except from those belonging to the families of Blenniidae, Gobiidae, and Tripterygiidae. Despite their important role in the ecology of shallow rocky reefs (Tiralongo et al, 2016), obtaining reliable diversity, density and biomass estimates for these highly diverse, small, crypto-benthic species would need a different type of sampling approach (e.g., Patzner, 1999;Tiralongo et al, 2016;Prato et al, 2017), which could not be followed due to fieldworkrelated logistical constraints.…”
Section: Field Protocolmentioning
confidence: 99%
“…All species were recorded except from those belonging to the families of Blenniidae, Gobiidae, and Tripterygiidae. Despite their important role in the ecology of shallow rocky reefs (Tiralongo et al, 2016), obtaining reliable diversity, density and biomass estimates for these highly diverse, small, crypto-benthic species would need a different type of sampling approach (e.g., Patzner, 1999;Tiralongo et al, 2016;Prato et al, 2017), which could not be followed due to fieldworkrelated logistical constraints.…”
Section: Field Protocolmentioning
confidence: 99%
“…They compared the two methods to find that HD video is a more cost-effective monitoring technique and indicated that HD video allows for effective fish identification by computer vision due to its larger screen size over UVC technology, as well as longer image analysis and more systematic operation. Prato, et al, applied UVC to monitor the fish combination of multiple sections in Marine reserve and can realize realistic assessment of the whole Marine fish composite structure [50].…”
Section: Captured Video Based On Computer Visionmentioning
confidence: 99%
“…grouper), and (3) transect C: 10 m x 1 m for crypto-benthic fishes (e.g. Gobidae) (Prato et al, 2017 for further methodological details) (see Suppl. mat.…”
Section: Sampling Design and Data Collectionmentioning
confidence: 99%
“…At each transect, each species encountered was identified and its abundance recorded. Fish size (total length) was recorded within 5 cm size classes for large sized fishes (species maximum size > 50 cm), 2 cm size classes for other necto-benthic fish species and 1 cm for small crypto-benthic fishes (following Prato et al, 2017). Based on density and size data, fish biomass was estimated using length-weight relationships (Froese & Pauly, 2017).…”
Section: Sampling Design and Data Collectionmentioning
confidence: 99%